Navigating Lung Cancer: Exploring Progress and Obstacles - A Comprehensive Review - Dorochowicz, Mateusz; Krzemienowska-Cebulla, Aleksandra; Matus, Iwona; Senat, Hanna; Madej, Aleksandra (Journal of Education, Health and Sport, 2024)
Lung cancer persists as a significant global health dilemma, characterized by elevated incidence and mortality rates worldwide. Despite recent strides in diagnostic methodologies, screening approaches, and therapeutic modalities, lung cancer retains its status as the foremost cause of cancer-related fatalities internationally. The disease is predominantly categorized into two primary forms: small-cell carcinomas and the notably more prevalent non-small-cell carcinomas, constituting approximately 85% of cases. While smoking stands as the primary risk factor for lung cancer, accounting for 80-90% of related deaths, other factors such as dietary habits, air pollution, genetic predisposition, and prior lung conditions play substantial roles. Diagnostic procedures encompass a range of techniques, including radiography, sputum cytology, bronchoscopy, biomarker analysis, among others. The imperative for progress and refinement in diagnostic tools, especially for early detection and monitoring in high-risk demographics, underscores the urgency. Continual research and enhancement of surgical, systemic, and localized treatments are indispensable in the battle against lung cancer. Despite advancements, challenges persist in achieving timely diagnoses, particularly in high-risk groups, and augmenting overall survival rates. This comprehensive review delves into current research advancements in lung cancer, with specific focus on classification, patient well-being, risk factors, diagnostic methodologies, and treatment options.